Pre-service teachers' voices of international teaching practicum in Indonesian elementary school - Setyaningsih, Ani; Diyanti, B. Yuniar; Nurhayati, Lusi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
International teaching practicums help pre-service teachers (PSTs) advance professionally in teaching and gain multicultural competence. This study aims at describing an investigation of challenges and problems faced by the pre-service teachers during their international teaching program in an Indonesian elementary school and how to cope with them revealed by the PSTs' voices. This qualitative case study started with conducting a survey questionnaire covering various aspects of results, challenges, and problems regarding the aspects of pedagogical, content knowledge, technology, and cultural gaps faced by 7 international pre-service teachers (PSTs) from the Netherlands. The survey results were then further examined through in-depth interviews with the PSTs and thematic analysis was conducted to examine the data. The findings showed that there were three categories of problems faced by the PSTs: issues from the students, problems from the PSTs, and problems from the schools or stakeholders. The PSTs could adapt to the situation and find solutions to the problems. They tried to be